A Semantic Framework for E-Commerce Using Web Ontology Language 2 - Jimoh, R.G.; Kinssinger, S.; Agbo, F.J.; AbdulRaheem, M.; Tomori, R.A.; Salimonu, I.R. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Several web applications have been deployed by business enterprises through which their products would not only bemade available on the internet, but also enable their prospective consumers to be able to follow some procedures to maketheir purchases online. This is normally achieved with the help of some technologies provided by the Semantic Web,namely Resource Description Framework (RDF), Resource Description Framework Schema (RDFS), DARPA AgentMarkup Language (DAML) plus Ontology Inference Layer (OIL) and Web Ontology Language (OWL1). The Presentstudy leverages on some of the Semantic Web technologies mentioned in the previous sentence in order to design aSemantic framework for enhancing Business to Consumer (B2C) e-commerce applications. In this paper, the researchersdeveloped OWL 2 ontology rich in more expressive OWL constructs for rich entailments. Qualified CardinalityRestriction (QCR) which OWL 2 is known for, is also applied to the ontology. Also in this paper, the researcherscompared two popular reasoners in querying the underlying ontology in a programmatic way. The overall aim of thisresearch is to provide a more efficient framework for B2C through the right choice and combination of some SemanticWeb languages.